2006
DOI: 10.2807/esm.11.01.00595-en
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of MRSA infections in horses in a veterinary hospital: strain characterisation and comparison with MRSA from humans

Abstract: Methicillin-resistant Staphylococcus aureus has become an emerging public health problem worldwide, no longer only associated with healthcare-associated infections. With the exception of some recent reports concerning infections in cats, dogs and horses, infections with MRSA in companion animals have been infrequently reported. Here we submit findings for MRSA infections in horses in a central European university hospital.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
3
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(74 citation statements)
references
References 26 publications
1
66
3
4
Order By: Relevance
“…Whereas with the assistance of epidemiological typing it is proved that strains of MRSA isolated from horses and equine associated personnel are different (Baptiste et al, 2005;O'Mahony et al, 2005;Weese et al, 2005a;Cuny et al, 2006). Outbreaks linking both horses and humans in veterinary hospitals were reported from the United States (Seguin et al, 1999), Canada (Weese et al, 2005a), Ireland (O'Mahony et al, 2005, Austria (Cuny et al, 2006(Cuny et al, , 2008, the Netherlands (van Duijkeren et al, 2010) Switzerland (Sieber et al, 2011) and Israel (Schwaber et al, 2013). The typing studies revealed that the MRSA isolated from pigs (Voss et al, 2005;Van Dijke et al, 2006) and cattle (Kwon et al, 2005) are distinct from MRSA of human lineage.…”
Section: Advances In Animal and Veterinary Sciencesmentioning
confidence: 99%
“…Whereas with the assistance of epidemiological typing it is proved that strains of MRSA isolated from horses and equine associated personnel are different (Baptiste et al, 2005;O'Mahony et al, 2005;Weese et al, 2005a;Cuny et al, 2006). Outbreaks linking both horses and humans in veterinary hospitals were reported from the United States (Seguin et al, 1999), Canada (Weese et al, 2005a), Ireland (O'Mahony et al, 2005, Austria (Cuny et al, 2006(Cuny et al, , 2008, the Netherlands (van Duijkeren et al, 2010) Switzerland (Sieber et al, 2011) and Israel (Schwaber et al, 2013). The typing studies revealed that the MRSA isolated from pigs (Voss et al, 2005;Van Dijke et al, 2006) and cattle (Kwon et al, 2005) are distinct from MRSA of human lineage.…”
Section: Advances In Animal and Veterinary Sciencesmentioning
confidence: 99%
“…The following are three different locations: (1) 60 harness racing-horses aged between [3][4][5][6] years randomly selected at the Agnano racetrack; (2) 64 breeding mares aged between [4][5][6][7][8][9][10][11][12][13][14][15] years from an Equine Reproduction Centre; (3) 67 horses aged more than 15 years from a large Riding Centre.…”
Section: Sample Collectionmentioning
confidence: 99%
“…Skin and soft tissue MRSA infections [7] , bacteraemia, septic arthritis and osteomyelitis [8,9] , implantrelated infections, metritis [10] , omphalitis [11] , catheter-related infections and pneumonia [12] have all been reported in horses.…”
Section: Introductionmentioning
confidence: 99%
“…This has recently been reviewed [1]. Sometimes distinct animal specific-lineages such as LA-MRSA have been involved [12,13], but on many occasions human-associated MRSA genotypes have been identified [14]. A note of caution in assessing the impact of 'animal' MRSA in human infections is that the increased awareness of such organisms is likely to have influenced the concentration of studies dealing with MRSA in animals.…”
Section: Emergence In Animalsmentioning
confidence: 99%
“…7% of horses on farms in Canada and the USA [63] were colonized with MRSA. Cuny et al [12] reported 24 MRSA infections in 768 clinical samples from horses at a veterinary teaching hospital in Austria and an estimated infection rate of 4.8 MRSA cases/1000 equine admissions. In a recent study investigating 110 horses presenting at a Belgian equine clinic 10 .…”
Section: Occurrence In Horsesmentioning
confidence: 99%